Myopia Is Related to Head Pain in Students of the Faculty of Medicine, Universitas Muhammadiyah Sumatera Utara - Arifin, Hasanul; Uljannah, Nisa (Universitas Muhammadiyah Sumatera Utara, 2025)
Abstract: Myopia was found to be a common cause of headaches, and about 28% of the patients studied had myopia. This study was conducted with the aim of finding out the relationship between myopia and headache in students with the target students of the Faculty of Medicine, Universitas Muhammadiyah Sumatera Utara. This study is an analytical observational research with a cross-sectional approach involving 72 research subjects of students of the Faculty of Medicine, Universitas Muhammadiyah Sumatera Utara, and using an online questionnaire with a Google form application to obtain primary data. Of the group of students who suffered from mild myopia, 23.5% suffered from mild headaches, 61.8% had moderate headaches, and 14.7% had severe headaches. Meanwhile, in the group of students who suffered from moderate myopia, 6.9% suffered from mild headaches, 58.6% moderate headaches and 34.5% severe headaches. For the group of students who suffer from severe myopia, no one experiences mild or moderate headaches, but there are 100% suffer from severe headaches. The Chi Square test shows the sum of 0.000. It can be concluded that myopia is related to headaches in medical students of the Universitas Muhammadiyah Sumatera Utara.